(untitled) (Journal of the College of Basic Education, 2022)
The research dealt with a theoretical framework that briefly explains the history of Arabic calligraphy and its various types. It also included the concept of formation in drawing the Arabic letter and the aesthetic values of the Arabic letter. It also dealt with the concept of formation and construction of the Arabic letter as an independent formal unit with its own structural laws. The Arabic letter in handcrafted industrial products such as the walls of mosques and others.As for digital designs, the researcher summarized their types and their importance in design and industry, and the research focused on giving a brief idea about the (3dsmax) program and its importance in design and industry, and included an explanation of the orders and operations that the researcher applied in the (3dsmax) program for the purpose of linking the formal concept the independent character of the Arabic character and the improvements that can be achieved using these operations and commands; To employ the Arabic letter as a formal unit to produce various industrial designs such as fences, windows, crockery and others so that the professional designer can apply these procedures to other letters to produce other products even if the designer is not a professional in Arabic script.The research included practical applications in the (3dsmax) program to convert the storage pattern (format) from a graphic pattern (JPG) to a formal pattern (3ds) by applying the formal poly line operations commands to convert the letter from a linear unit to an area unit and its two sizes (there is no procedure Similar to previous according to the knowledge of the researcher) so that the (3dsmax) program can deal with its modifications (modifies) on the character as an area unit and then its volumes to accomplish industrial designs, these practical procedures using digital technologies will have industrial design outputs and effective capabilities in modular production because the program has links and Extensions with prototyping machines and most of the various devices that use digital technology in industrial production, including cutting and milling devices. The research included a design proposal for the purpose of confirming theoretical and applied results.